A Systematic Review of Barriers and Facilitators to Minority Research Participation Among African Americans, Latinos, Asian Americans, and Pacific Islanders - George, Sheba; Duran, Nelida; Norris, Keith (American journal of public health (1971), 2014)
To assess the experienced or perceived barriers and facilitators to health research participation for major US racial/ethnic minority populations, we conducted a systematic review of qualitative and quantitative studies from a search on PubMed and Web of Science from January 2000 to December 2011. With 44 articles included in the review, we found distinct and shared barriers and facilitators. Despite different expressions of mistrust, all groups represented in these studies were willing to participate for altruistic reasons embedded in cultural and community priorities. Greater comparative understanding of barriers and facilitators to racial/ethnic minorities’ research participation can improve population-specific recruitment and retention strategies and could better inform future large-scale prospective quantitative and in-depth ethnographic studies.